Оцінка прямих втрат металу при продувці в конвертері засобами низькотемпературного моделювання та її верифікація - Молчанов, Л.С.; Голуб, Т.С.; Дудченко, С.О.; Семикін, С.І. (Physico-technological Institute of Metals and Alloys, 2025)
World steel production in oxygen converters has high indicators, which are maintained due to constant process of improvements. The simplest from the point of view of implementation is to improve the design of the top blowing device – the blowing lance, and develop technology for its use. This feature is due to the key impact of the specified device on the process: the creation of high-speed oxygen jets that have a mixing effect on the liquid metal bath and ensure the flow of chemical processes. The physical study of the characteristics of new devices and verification of the efficiency of their operation during blowing under conditions of interaction with the liquid bath are important in this improvement process. Most often, the method of physical low-temperature modeling is chosen for verification due to the availability of materials, ease of implementation and high clarity. Water and oil are used as modeling liquid media to simulate metal and slag melts, and air as a gaseous medium. An important condition for modeling is compliance with the criteria of geometric similarity and similarity of physical processes through the Froude and Weber criteria. However, even their use does not guarantee the quantitative similarity of the obtained results to the real process. In this regard, it is important to accumulate information on the correlation of the results of physical low-temperature and high-temperature modeling methods under the conditions of using the same blowing devices and technological features of blowing. The article presents the results of a comparative analysis of low- and high-temperature modeling of the top blowing of a liquid bath through a four-nozzle lance in order to evaluate the indicator of direct metal losses (spatter of the metal phase under the action of a gas jet). It was established that in low-temperature modeling, the level of losses due to spatter is significantly higher than in the blowing of a real metal melt due to significantly lower indicators of the physical properties of the modeling fluid. It was also noted that the most appropriate period under two-phase modeling conditions for real blowing is the beginning or end of blowing, when foaming depends more on the action of the gas jet due to the difficulty of providing conditions on a low-temperature model similar to the additional effect on foaming of the carbon oxidation reaction in the melt.